Sleeve Gastrectomy and Gastroesophageal Reflux Disease - Michael Laffin; Johnny Chau; Richdeep S. Gill; Daniel W. Birch; Shahzeer Karmali (Journal of Obesity)
Bariatric surgery, when combined with lifestyle and medical interventions, is a common and successful treatment modality in the obese patient. Laparoscopic sleeve gastrectomy is one such procedure that has increased in popularity as a definitive bariatric operation. Although laparoscopic sleeve gastrectomy has been shown to be effective in producing weight loss and improving type 2 diabetes mellitus, its effect on gastroesophageal reflux disease (GERD) has been inconsistent. This paper aims to summarize the available literature regarding GERD prevalence following laparoscopic sleeve gastrectomy, 8 studies demonstrate increased GERD prevalence, and 5 demonstrate decreased GERD prevalence following laparoscopic sleeve gastrectomy. The relationship between GERD and SG is complex and no clear relationship exists. The anatomic and physiologic changes caused by laparoscopic sleeve gastrectomy are discussed in the context of these inconsistent results.